REVITALISASI SEKTOR PERTANIAN MELALUI PEMBERDAYAAN - Ono Taryono (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
The majority of Indonesians, especially those in rural areas, live dependently on agricultural sector. Agricultural sector indisputably caters for most employment opportunities in the country; however, it is hitherto unable to raise farmers’ well-being. It stumbles upon several problems which are to be eliminated. The problems include farming land, capital access, technology, human resource capacity, infrastructure, market access and institutional management. Therefore, agriculturalrevitalization through empowerment becomes a prerequisite if the agricultural sector is to be elevated from its long-sustained deprivation